Partitions: A taxonomy of types and representations and an overview of coding techniques - de Sequeira, Manuel Menezes; Cortez, Diogo (Signal processing. Image communication, 1997)
Recognising the importance of partition or shape coding in the field of image and video coding, and the fact that a systematisation of the subject would simplify the comparison of partition coding techniques, this paper proposes a classification of partition types and partition representations into a taxonomy tree. The partition type level of the tree classifies the possible partition types that may have to be coded. The partition representation level classifies the possible representations for each partition type. This paper also overviews the partition coding techniques which address the considered partition types and which use the identified partition representations. Emphasis is given to binary partition coding techniques proposed within the framework of MPEG-4.